The effect of creatine monohydrate supplementation on sprint skating in ice-hockey players - Cornish, S. M.; Chilibeck, P. D.; Burke, D. G. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: Creatine monohydrate supplementation is beneficial for enhancing high-intensity exercise performance, especially activities that involve repeated sprints. Creatine monohydrate supplementation is common in ice-hockey players. The purpose of this study was to determine the effect of creatine monohydrate supplementation on sprint skating performance in Junior B and collegiate ice-hockey players. Methods: Seventeen ice-hockey players were randomly assigned to receive creatine (0.3 g/kg body mass/day for 5 days) or placebo. Before and after supplementation players performed repeated sprints to exhaustion on a skating treadmill (repeated 10-s sprints; 30-s rest between sprints) while blood lactate was simultaneously collected. The time to exhaustion on the treadmill test was calculated as total amount of time, including partial intervals, before the player reached exhaustion. Players were also tested for peak torque and average power during knee extension/flexion (3 sets of 10 reps; 60-s rest between sets) on an isokinetic dynamometer at 60 degrees/s. Results: The change in time to exhaustion from before to after supplementation averaged 20.6±7 s in the creatine group and 21.9±13 s in the placebo group, with no differences between groups. Likewise, there were no differences between groups for changes in isokinetic peak torque and average power. There were no differences between groups over time for blood lactate changes during the repeated sprints on the treadmill. Conclusion: We conclude that creatine was not effective for improving performance in these ice-hockey players.